Flexible AC Transmission Systems: Modelling and Control - Zhang, Xiao-Ping.; Rehtanz, Christian; Pal, Bikash; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This monograph presents advanced modelling, analysis and control techniques of FACTS. These topics reflect the recent research and development of FACTS controllers, and anticipate the future applications of FACTS in power systems. The book covers comprehensively a range of power-system control problems: from steady-state voltage and power flow control, to voltage and reactive power control, to voltage stability control, to small signal stability control using FACTS controllers. The book presents the modelling of the latest FACTS controllers for power flow control, compensation and power quality (IPFC, GUPF, VSC HVDC and M-VSCHVDC, etc.) in power system analysis. The selection is evaluated by the actual and likely future practical relevance of each. The material is derived mainly from the research and industrial development in which the authors have been heavily involved. The book is timely and of great value to power engineering engineers and students of modelling, simulations and control design of FACTS for a broad practical range of power system operation, planning and control problems.
FACTS-Devices and Applications -- Modeling of Multi-Functional Single Converter FACTS in Power Flow Analysis -- Modeling of Multi-Converter FACTS in Power Flow Analysis -- Modeling of FACTS-Devices in Optimal Power Flow Analysis -- Modeling of FACTS in Three-Phase Power Flow and Three-Phase OPF Analysis -- Steady State Power System Voltage Stability Analysis and Control with FACTS -- Steady State Voltage Stability of Unbalanced Three-Phase Power Systems -- Congestion Management and Loss Optimization with FACTS -- Non-Intrusive System Control of FACTS -- Autonomous Systems for Emergency and Stability Control of FACTS -- Wide Area Control of FACTS -- Modeling of Power Systems for Small Signal Stability Analysis with FACTS -- Linear Control Design and Simulation of Power System Stability with FACTS -- Power System Stability Control with FACTS Considering Multiple Operating Points -- Power Electronic Control for Wind Generators.
Keywords: Engineering; Electronics; Production of electric energy or power; Electric engineering; Engineering; Power Electronics, Electrical Machines and Networks; Energy Technology; Control, Robotics, Mechatronics; Electronics and Microelectronics, Instrumentation; Computational Intelligence; Energy, general